N3RS De' Art - Sounam, Rolandez; Abidin, Nik Fazilah; Omar, Siti Halimah; Jamlan, Nazierra; Hamdan, Nur Farah Arqilah (2014)
N3RS De' Art Company is a business of photography and the business will start at the end of October 2015. Services that will be provided are photo shoot session, editing photos, photo booth decoration for any events such as wedding or birthday and classes for editing lesson. This business located at Level 1, 1 Borneo Hypermall Kota Kinabalu Sabah. The location is a strategic place for our business since it become a spot of people to go or hanging out. Therefore, it will have a great potential market for this business. We believe that our business have potential in this millennium especially in urban area because people are always looking for a better service at this area. Moreover, population and growth of people are getting higher and they are for sure will plan for marriage and any event. Another factors that influencing us to choose this photography service is because in Kota Kinabalu, the people are most likely love to take photo and do editing as the trending for nowadays and it make it easier for us as a new entrepreneur to engage in the business.